2002
DOI: 10.1002/ar.10066
|View full text |Cite
|
Sign up to set email alerts
|

Belief vs. scientific observation: The curious story of the precardiac mesoderm

Abstract: The retinas of three species of shrews (Sorex araneus, S. coronatus, and S. minutus) were analyzed. Two kinds of photoreceptors were identified according to (among other characteristics) the traits of the mitochondria of their inner segments. The rod inner segments contained several round or oval mitochondria distributed longitudinally inside the ellipsoid. The cone inner segment showed a few mitochondria, which we classified as megamitochondria (maximum length = 4.22 μm in S. araneus, 5.68 μm in S. coronatus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Although this rostral marginal crescent is thought to be 'a feature common to many mammals' , further studies, particularly in the human, need to be undertaken. Further possible characteristics of rostral crescents are suggested by the Nkx2.5-positive domain in the chick embryo at HH5 [Eisenberg, 2002, fig. 1A].…”
Section: Early Stagesmentioning
confidence: 89%
“…Although this rostral marginal crescent is thought to be 'a feature common to many mammals' , further studies, particularly in the human, need to be undertaken. Further possible characteristics of rostral crescents are suggested by the Nkx2.5-positive domain in the chick embryo at HH5 [Eisenberg, 2002, fig. 1A].…”
Section: Early Stagesmentioning
confidence: 89%
“…When Nkx2.5 expression in the chick embryo was first described, it was suggested that this molecule is first exhibited by precardiac cells as early as HH stage 5. However, it now appears that the Nkx2.5-positive cells within the HH stage 5 embryo are not cells that will contribute to the heart, as the recent cardiac fate map generated by Redkar et al (2001) clearly indicates that the Nkx2.5 domain does not coincide with the heart-forming fields until HH stage 6 (Eisenberg, 2002). Instead, it is likely that the Nkx2.5-expressing cells at HH stage 5 are either endoderm or ectoderm, which would be consistent with the demonstration that Nkx2.5 is expressed in all three germ layers within an HH stage 6 embryo (Schultheiss et al, 1995).…”
Section: The Molecular Phenotype Of Precardiac Stem Cellsmentioning
confidence: 98%
“…Since markers for these stem cells have not been described, the only way to confront this objection would be to plate individual cells at clonal density and look at their differentiated progeny. To study the properties of myocardial progenitors in the embryo, the clonal stem cell line QCE6 was derived from precardiac mesoderm of HH stage 4 quail embryos (Eisenberg andBader, 1995, 1996). As may be expected considering their precardiac mesoderm origin, QCE6 cells are able to give rise to cardiomyocytes (Fig.…”
Section: Commitment Of Precardiac Stem Cellsmentioning
confidence: 99%
“…Moreover, in chicken, isl-1 expression in the primary heart field precedes the expression of Nkx2.5. (23,24) Interestingly, the D4.25 bry þ /Flk-1 þ cell population is also positive for MesP1, which is expressed in the nascent heart precursor cells in the embryo and has also been suggested to be involved in the specification of endothelial lineages. (21,22) Probably due to technical limitations, the issue of when the two heart field lineages segregate is difficult to resolve in the mouse embryo.…”
Section: Nkx25mentioning
confidence: 99%